The impact of the coronary sinus reducer upon left ventricular function in patients with refractory angina pectoris. Issue 6 (2nd August 2019) - Tzanis, Georgios; Palmisano, Anna; Gallone, Guglielmo; Ponticelli, Francesco; Baldetti, Luca; Esposito, Antonio; Colombo, Antonio; Giannini, Francesco
Abstract: Objectives: To evaluate the impact of coronary sinus (CS) Reducer implantation upon left ventricular (LV) function. Background: CS Reducer implantation is associated with symptomatic relief in patients with refractory angina. The effects of the device upon left ventricular function remains unknown. Methods: Prior to device implantation and at 4‐months, resting ventricular volumes and function were measured using cardiac magnetic resonance (CMR). Stress CMR was performed to extract quantitative indices of myocardial perfusion (myocardial perfusion reserve index‐MPRI). Results: Nineteen patients (18 males, 66.0 [IQR 56.0–77.0] years), underwent successful Reducer implantation. Sixteen (84%) patients improved by at least 1 CCS class. Four months after Reducer implantation, we noticed a significant improvement in LV ejection fraction (LVEF) (61 [IQR 47–71] to 66 [IQR 57–72] %; p = .009), a reduction in LV end‐diastolic volume (LVEDV)/Body surface area (BSA) (65.7 [IQR 57.4–89.6] to 64.7 [IQR 53.7–74.1] mL/m 2 ; p = .036) and a reduction in LV end‐systolic volume (LVESV)/BSA (28.7 [IQR 18.6–38.8] to 20.0 [IQR 15.0–31.4] mL/m 2 ; p = .007). Patients with reduced EF (EF < 50%, n = 6) presented a greater increase of EF at follow up compared to patients with preserved EF (11.3 [IQR 6.5–54.5] vs. 3.8 [IQR 0.6–9.1] %; p = .029). The observed decrease in LVESV/BSA was greater in patients with reduced EF (23.6 [IQR 11.6–33.8] vs. 4.2 [IQR −2.0 to 8.4] mL/m 2 ; p = .005). A significant increase in transmural MPRI was observed 4 months after Reducer implantation ( p < .011). Conclusions: CS Reducer improved angina symptoms and improved left ventricular function. The improvement was pronounced in the subgroup of patients with reduced ejection fraction. Myocardial perfusion improvement could represent the underlying mechanism for the observed benefits.